2012
DOI: 10.1787/5k9fq23507vc-en
|View full text |Cite
|
Sign up to set email alerts
|

School Choice and Equity

Abstract: This paper was prepared as part of the OECD thematic review Overcoming School Failure: Policies that Work, www.oecd.org/edu/equity. The project provides evidence on the policies that are effective to reduce school failure by improving low attainment and reducing dropout, and proactively supports countries in promoting reform. The project builds on the conceptual framework developed in the OECD's No More Failures: Ten Steps to Equity in Education (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 66 publications
(30 reference statements)
0
31
0
2
Order By: Relevance
“…Many countries of the Organisation for Economic Co-operation and Development (OECD) are working to increase choice and competition in the educational system (Musset, 2012). The process of choosing schools is complicated, and there is no consensus on a set of specific factors and methods to analyze such choices.…”
Section: Top Reasons For Choosing Schoolsmentioning
confidence: 99%
“…Many countries of the Organisation for Economic Co-operation and Development (OECD) are working to increase choice and competition in the educational system (Musset, 2012). The process of choosing schools is complicated, and there is no consensus on a set of specific factors and methods to analyze such choices.…”
Section: Top Reasons For Choosing Schoolsmentioning
confidence: 99%
“…The children of immigrants are hit hard, both because they are over-represented in disadvantaged schools ( Figure 14) and because the effect of school disadvantage on learning outcomes tends to be larger than for students with no immigrant background (OECD, 2012b). In both the Flemish and French Communities, free choice of primary and secondary schools, with enrolment largely unregulated until the past decade, has likely contributed to school segregation, which often exceeds residential segregation, especially in Brussels (Musset, 2012;Cantillon, 2013). In welcome steps, the authorities have introduced controlled choice schemes, which supplement free choice with allocation mechanisms to increase social diversity in schools.…”
Section: Promoting Social Diversity In Schoolsmentioning
confidence: 99%
“…The same possibility of choosing at any time a different public school, based on its perceived status as a less demanding or more protective context, is significantly at work. Almost 80% of the head teachers in a study by Musset (2012) reported that there are two or more lower-secondary schools (and almost 90% reporting at least one school), including privateparitarie, competing in the same area. Notably, Italy ranked 5 th out of 34 countries in terms of number of alternatives available in a given territory, just before the United Kingdom 6 .…”
Section: The Disarticulation Of a Welfarist Institutionmentioning
confidence: 99%